2020
DOI: 10.3389/fnins.2020.00831
|View full text |Cite
|
Sign up to set email alerts
|

Maresin 1 Attenuates Radicular Pain Through the Inhibition of NLRP3 Inflammasome-Induced Pyroptosis via NF-κB Signaling

Abstract: Background: The exposure of the nucleus pulposus (NP) causes an immune and inflammatory response, which is intrinsically linked to the pathogenesis of radicular pain. As a newly discovered pro-resolving lipid mediator, maresin 1 (MaR1) could exert powerful inflammatory resolution, neuroprotection, and analgesic activities. In the present research, the analgesic effect of MaR1 was observed. Then, the potential mechanism by which MaR1 attenuated radicular pain was also analyzed in a rat model. Methods: Intrathec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 52 publications
(80 reference statements)
2
21
0
Order By: Relevance
“…To further confirm the presence of pyroptosis in C. albicans -infected mouse corneas, we performed double-immunofluorescence staining. Active CASP1 and TUNEL double positive cells were designated as pyroptotic cells ( 25 ). As shown in Figure 2D , pyroptotic cell death was obviously observed in C. albicans -infected corneas, in contrast, no pyroptotic cell was observed in control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm the presence of pyroptosis in C. albicans -infected mouse corneas, we performed double-immunofluorescence staining. Active CASP1 and TUNEL double positive cells were designated as pyroptotic cells ( 25 ). As shown in Figure 2D , pyroptotic cell death was obviously observed in C. albicans -infected corneas, in contrast, no pyroptotic cell was observed in control group.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, increasing evidences have shown that the DNA fragmentation during pyroptosis can be labeled by TUNEL-staining ( 28 , 29 ). Therefore, the active CASP1 and TUNEL double-immunofluorescence staining was widely used to detect pyroptosis ( 24 , 25 , 30 ). We found that pyroptotic cells was obviously observed in C. albicans -infected mouse corneas according to CASP1 and TUNEL double-immunofluorescence staining.…”
Section: Discussionmentioning
confidence: 99%
“…Maresin-1 has also been shown to be effective in chronic pain, when administered between the L4 and L6 vertebrae of the spinal cord and the analgesic effect was observed for 5 days [40]. Regarding the mechanisms, maresin-1 decreased proinflammatory cytokines (IL-1β, IL-18, and TNFα) and reduced NLRP3 inflammasome, leading to the impairment of cell death and positive activation of NF-κB/p65-mediated inflammation and pain [41]; the mechanical and thermal hypersensitivity enhanced the IL-1β and IL-18 levels and the expression of NLRP3 inflammasome components, which were markedly suppressed by maresin-1 treatment [42].…”
Section: Painmentioning
confidence: 99%
“…Intrathecal administration of MaR 1 inhibits the activation of DRG neurons and abates activation of spinal NF-kB and production of TNF-α and IL-1β, resulting in reduced mechanical and thermal hyperalgesia in CFA- and carrageenan-induced pain paradigms, up to 3–5 days after the treatment ( Fattori et al, 2019 ) and in spinal nerve ligation models ( Gao et al, 2018 ). MaR 1 also reduces mechanical allodynia in rat models of radicular pain ( Wang et al, 2020 ), as well as chemotaxis of inflammatory cells in the calcitonin gene-related peptide (CGRP)-releasing DRG neurons ( Fattori et al, 2019 ). In line with this, a recent investigation has shown that intraperitoneal administration of MaR 1 in a K/BxN transfert-based model of arthritic pain led to reduced mechanical hypersensitivity, due to inhibition of macrophage inflammatory chemotaxis in the DRG ( Allen et al, 2020 ).…”
Section: Spms In Painmentioning
confidence: 99%